2004
DOI: 10.1073/pnas.0406598101
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative extraction of membrane nanotubes by molecular motors

Abstract: In eukaryotic cells, nanotubes represent a substantial fraction of transport intermediates between organelles. They are extracted from membranes by molecular motors walking along microtubules. We previously showed that kinesins fixed on giant unilamellar vesicles in contact with microtubules are sufficient to form nanotubes in vitro. Motors were attached to the membrane through beads, thus facilitating cooperative effects. Koster et al. proposed that motors could dynamically cluster at the tip of tubes when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
248
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(267 citation statements)
references
References 27 publications
16
248
3
Order By: Relevance
“…The Kinesin motors along the bulk of membrane tube are moving freely in a fluid lipid bilayer, do not feel any force, and may walk at maximum speed toward the membrane tube tip. However, the motors at the tip experience the load of the membrane tube and their speeds are damped (7,8,16). The Gaussian-like distribution of speeds we find for Kinesin elucidates the influence of load on the cluster of motors accumulating at the tip of the membrane tube.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The Kinesin motors along the bulk of membrane tube are moving freely in a fluid lipid bilayer, do not feel any force, and may walk at maximum speed toward the membrane tube tip. However, the motors at the tip experience the load of the membrane tube and their speeds are damped (7,8,16). The Gaussian-like distribution of speeds we find for Kinesin elucidates the influence of load on the cluster of motors accumulating at the tip of the membrane tube.…”
Section: Resultsmentioning
confidence: 80%
“…Colocalization of these membrane tubes with the underlying cytoskeleton has led to the finding that cytoskeletal motor proteins can extract membrane tubes (6). Motors must work collectively to extract membrane tubes (7,8), because the force needed to form a tube, F tube (9), is larger than the mechanical stall force of an individual motor (10).…”
mentioning
confidence: 99%
“…Several studies in which network formation was observed on a glass surface demonstrated a direct role for microtubules and microtubule motors in tubule formation (reviewed in [2]). Recently, two groups [40,41] have analyzed tubule generation from giant unilamellar lipid vesicles tethered to microtubules via microtubule motors. Interestingly, in the presence of energy and in the absence of any other additional proteins, branching tubules were readily created in these in vitro systems.…”
Section: In Vitro Reconstitution Of Tubular Networkmentioning
confidence: 99%
“…All the available models for the oscillatory movement of the chromosome (often referred to as "kinetochore directional instability" [8]) have as a common feature that the kinetochore somehow controls the switching between P and AP phases [8,9,10,11]. However, the collective behavior of molecular motors can give rise to dynamical instabilities [14] which have been observed in biological and biomimetic systems [15,16]. Indeed, inhibiting chromokinesin activity leads to the disappearance of the oscillations and to the collapse of mono-oriented chromosomes onto the centrosome [4].…”
mentioning
confidence: 99%